2014
DOI: 10.1063/1.4863463
|View full text |Cite
|
Sign up to set email alerts
|

Flow strength of tantalum under ramp compression to 250 GPa

Abstract: Compressibility and strength of nanocrystalline tungsten boride under compression to 60GPaStrength and elastic moduli of TiN from radial x-ray diffraction under nonhydrostatic compression up to 45 GPa Modeling of the elastic precursor behavior and dynamic inelasticity of tantalum under ramp wave loading to 17 GPa A magnetic loading technique was used to study the strength of polycrystalline tantalum ramp compressed to peak stresses between 60 and 250 GPa. Velocimetry was used to monitor the planar ramp compres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 50 publications
6
50
0
Order By: Relevance
“…As a proof of principle, we re‐examine previously published measurements on tantalum (Ta) generated with pulsed magnetic fields (Brown et al ., ), accounting for previously ignored sources of uncertainty. Because these experiments have been analysed by using traditional analytic techniques, we can compare the computational simulation approach with the analytic technique to test whether the new approach results in similar inferences as well as quantify the effect of accounting for previously ignored sources of uncertainty.…”
Section: Experimental Configuration and Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…As a proof of principle, we re‐examine previously published measurements on tantalum (Ta) generated with pulsed magnetic fields (Brown et al ., ), accounting for previously ignored sources of uncertainty. Because these experiments have been analysed by using traditional analytic techniques, we can compare the computational simulation approach with the analytic technique to test whether the new approach results in similar inferences as well as quantify the effect of accounting for previously ignored sources of uncertainty.…”
Section: Experimental Configuration and Modellingmentioning
confidence: 99%
“… Experimental measurements considered in this study and reported previously by Brown et al . (); each colour represents a different experiment…”
Section: Experimental Configuration and Modellingmentioning
confidence: 99%
“…The SC and NC Ta systems were found to have an initial average dislocation density of 2.35×10 16 m −2 and 1.49×10 16 m −2 respectively. These dislocation densities, while much higher than the expected dislocation densities in the high pressure experimental Ta samples [1,3], are within an order of magnitude of experimental measurements for heavily cold-worked polycrystalline and nanocrystalline metals [14,15]. FIGURE 2.…”
Section: Methodsmentioning
confidence: 86%
“…Recently, Brown et al [1] obtained strength values for tantalum (Ta) at 250 GPa and an average strain-rate of 3 × 10 5 s 1 during quasi-isentropic compression experiments that were well above previously accepted models, and demonstrated that changes in the initial microstructure resulted in changes in strength. The self-consistent Lagrangian analysis technique used by Brown et al [1] to extract strength was validated by Moore et al [2] using molecular dynamics (MD) techniques and provides credence to the finding that the dynamic strength is influenced by initial microstructure. However, Park et al [3] found Ta strength at 130 GPa and an average strain-rate of 1 × 10 7 s 1 to be independent of grain size during Rayleigh-Taylor instability growth experiments.…”
Section: Introductionmentioning
confidence: 90%
“…have attracted much attention because of interesting phenomena and great challenges to experiment and simulation. A number of experiments have shown that the dynamic yield strength of metals depends on loading pressure and rates very sensitively [1][2][3]. Techniques for strength measurement at high pressures include comparison to hydrostatic response, lateral stress gauges, growth of Rayleigh-Taylor instabilities [4,5], etc..…”
Section: Introductionmentioning
confidence: 99%